Foreign and domestic takeovers in Germany: First comparative evidence on the post-acquisition target performance using new data - John P. Weche Gelübcke (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This study provides the first comparative evidence of foreign and domestic acquisitions in Germany. A propensity score matching approach combined with a difference-in-difference estimator were performed separately for foreign and domestic acquisitions to account for a general takeover effect. The study is based on new high-quality panel data for manufacturing enterprises, provided by German official statistics. The results indicate a negative impact of foreign takeovers on employment and no productivity improvements for the period 2007 to 2009. This evidence contradicts existing empirical studies for Germany which find significant productivity improvements and no changes in terms of employment. These findings are of particular interest to Germany as one of the most important FDI in ow destinations worldwide. They contribute to the foreign ownership performance premium literature as well as improving the understanding of foreign acquisition consequences, a subject of utmost topicality.
Keywords: F21; F23; G34; 330; post-acquisition performance; foreign takeover; manufacturing; treatment analysis; Germany; Übernahme; Multinationales Unternehmen; Direktinvestition; Ausländisch; Unternehmenserfolg; Produktivität; Beschäftigungseffekt; Deutschland